Penjaminan Keberlanjutan Pembangunan Kapal Kayu Melalui Pelatihan Pembuatan Pola Gading untuk Penerapan Inovasi Gading Baja Sebagai Pengganti Gading Kayu bagi Pengrajin Kapal Kayu di Kabupaten Takalar - Mohammad Rizal Firmansyah; Lukman Bochary; Syamsul Asri; Muhammad Rusydi Alwi; Misliah Idrus; Ganding Sitepu; Wihdat Djafar; Rosmani - (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2019)
Currently wood raw material used for ivory or wooden ship frames is increasingly difficult to obtain because it has a special shape, where the wood for the ship's ivory must be taken from the tree in the form of curved beams, so that it is easily shaped according to the shape of the wooden ship that will be built. Some wooden ship craftsmen in South Sulawesi have faced this difficulty. One of them is a wooden ship craftsman who is part of a group of wooden ship craftsmen "TORANI" in Galesong Kota Village, Galesong District, Takalar. This group of craftsmen specifically produces fishing vessels with sizes of 10 GT to 30 GT. To overcome this problem, an alternative solution for wood ivory is needed. A study has found an alternative substitute for wood ivory, namely steel, with dimensions suitable for use on fishing vessels of 10 GT, 20 GT, and 30 GT. The dimensions of the steel ivory obtained are close to the wood ivory but with greater strength. To be able to apply the steel ivory to the wooden ship, the partner craftsmen need to be trained in its use, starting from pattern taking, making and installing steel ivory. The target of partner activities in this service activity is in the first stage of the process of applying steel ivory to wooden ships, which is capable of making steel ivory patterns. This pattern will later be used as the basis for making steel ivory on the wooden ships they built. The method of the activity carried out was training and mentoring for partner members to make steel ivory patterns in two stages as follows: The first stage was counseling and introduction to partners regarding steel ivory as a substitute for wood ivory; and the second stage is the practice and accompaniment of technology for making steel ivory patterns. The second stage includes guiding participants using equipment and equipment for making ivory patterns and guiding the practice of making steel ivory patterns taken from the shape of wooden ships by following the curves of the wooden ship's skin.